Methylglyoxal accumulation de-regulates HoxA5 expression, thereby impairing angiogenesis in glyoxalase 1 knock-down mouse aortic endothelial cells - Nigro, Cecilia; Fleming, Thomas; Nawroth, Peter Paul (Biochimica et biophysica acta. Molecular basis of disease, 2019)
Impaired angiogenesis leads to long-term complications and is a major contributor of the high morbidity in patients with Diabetes Mellitus (DM). Methylglyoxal (MGO) is a glycolysis byproduct that accumulates in DM and is detoxified by the Glyoxalase 1 (Glo1). Several studies suggest that MGO contributes to vascular complications through mechanisms that remain to be elucidated. In this study we have clarified for the first time the molecular mechanism involved in the impairment of angiogenesis induced by MGO accumulation. Angiogenesis was evaluated in mouse aortic endothelial cells isolated from Glo1-knockdown mice (Glo1KD MAECs) and their wild-type littermates (WT MAECs). Reduction in Glo1 expression led to an accumulation of MGO and MGO-modified proteins and impaired angiogenesis of Glo1KD MAECs. Both mRNA and protein levels of the anti-angiogenic HoxA5 gene were increased in Glo1KD MAECs and its silencing improved both their migration and invasion. Nuclear NF-ĸB-p65 was increased 2.5-fold in the Glo1KD as compared to WT MAECs. Interestingly, NF-ĸB-p65 binding to HoxA5 promoter was also 2-fold higher in Glo1KD MAECs and positively regulated HoxA5 expression in MAECs. Consistent with these data, both the exposure to a chemical inhibitor of Glo1 “SpBrBzGSHCp2” (GI) and to exogenous MGO led to the impairment of migration and the increase of HoxA5 mRNA and NF-ĸB-p65 protein levels in microvascular mouse coronary endothelial cells (MCECs). This study demonstrates, for the first time, that MGO accumulation increases the antiangiogenic factor HoxA5 via NF-ĸB-p65, thereby impairing the angiogenic ability of endothelial cells.
Available online 18 October 2018
Gesehen am 31.07.2019